2021
DOI: 10.2147/jir.s334581
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Contributes to Host Defense Against Klebsiella pneumoniae-Induced Liver Abscess

Abstract: Purpose: Klebsiella pneumoniae-induced liver abscess (KLA) is a type of pyogenic liver abscess (PLA), which is a distinct invasive syndrome that has been increasingly reported worldwide over the past two decades. The intestinal microbiota is increasingly recognized as an important modulator that can promote and maintain host immune homeostasis. However, its precise role in liver abscess is unknown. We aimed to investigate the function of the gut microbiota in the host defense against K. pneumoniae infection. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Previous studies have consistently indicated that the administration of levofloxacin can disturb the equilibrium of the intestinal microbiota, thereby inducing antibiotic-associated inflammation within the gastrointestinal tract [ 55 ]. Moreover, previous research conducted by our team and other scholars has provided evidence that the depletion of the intestinal microbiota resulting from the administration of antimicrobial drugs substantially elevates the likelihood of bacterial infectious diseases [ 53 , 54 , 72 74 ]. This correlation is closely linked to the reduction of immunoregulatory metabolites derived from the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have consistently indicated that the administration of levofloxacin can disturb the equilibrium of the intestinal microbiota, thereby inducing antibiotic-associated inflammation within the gastrointestinal tract [ 55 ]. Moreover, previous research conducted by our team and other scholars has provided evidence that the depletion of the intestinal microbiota resulting from the administration of antimicrobial drugs substantially elevates the likelihood of bacterial infectious diseases [ 53 , 54 , 72 74 ]. This correlation is closely linked to the reduction of immunoregulatory metabolites derived from the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The perturbation of the gut microbiota resulting from the administration of antimicrobial agents is linked to dysregulation of the host immune system, thereby heightening vulnerability to diverse bacterial infections [53,54]. Prior investigations have unequivocally established that the modification of the gut microbiota composition brought about by levofloxacin intensifies the inflammatory reactions of the host [55].…”
Section: Maintenance Of Gut Microbiota Structurementioning
confidence: 99%
“…Hv-Kp usually colonize the gastrointestinal (GI) tract [15], and, under certain circumstances (as for example, antibiotic-induced dysbiosis), they may spread to other organs and apparatus [16,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the gut and liver is established by the gut-liver axis through the vascular path of the portal vein system that transfers gutderived metabolites directly to the liver and carries bile and antibody excreted from the liver to the intestine (Albillos et al, 2020). A variety of acute and chronic liver diseases, including pyogenic liver abscess (Zheng et al, 2021), nonalcoholic fatty liver disease (Boursier et al, 2016), alcoholassociated liver disease (Gu et al, 2021), and drug-induced liver injury (Gong et al, 2018(Gong et al, , 2021 are closely linked to disordered gut microbiota. We speculated that the gut flora may be one important switch of the host response to IAHrelated liver injury due to the reason that IAH leads to gut microbiota dysbiosis, which plays a critical role in the polymicrobial sepsis-induced liver injury (Gong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%